Giant Inflatable Colon and Community Knowledge, Intention, and Social Support for Colorectal Cancer Screening - Redwood, Diana (Centers for Disease Control and Prevention, 2013)
INTRODUCTION: Colorectal cancer (CRC) is the second-leading cause of deaths from cancer in the United States. Screening decreases CRC deaths through early cancer detection and through removal of precancerous lesions. We investigated whether a health exhibit consisting of a giant inflatable colon was an effective educational tool to increase community members’ knowledge, intention, and social support for CRC screening and prevention. METHODS: Alaska adults (N = 880) attending community events statewide from March 2011 through March 2012 completed a short survey to assess knowledge about CRC, intention to get screened, and level of social support before and after walking through a giant interactive model of a human colon. The survey used a combination of open-ended questions and a Likert scale, where 1 was “very unlikely,” 2 was “somewhat unlikely,” 3 was “neutral,” 4 was “somewhat likely,” and 5 was “very likely.” The model depicted CRC stages from normal tissue to advanced adenocarcinoma and displayed signs with CRC prevention tips. We used the McNemar test and paired sample t tests for univariate analyses. RESULTS: Respondents significantly improved their CRC knowledge (P < .05), intention to get screened (mean score increased from 4.3 to 4.5, P < .001), and comfort with talking to others about CRC screening (mean level of comfort increased from 3.8 to 3.9, P < .001). Multivariate analysis showed no significant differences by sex, age, or race for improvements in CRC screening knowledge, intention, or comfort. CONCLUSION: Interactive exhibits can improve public knowledge and interest in CRC screening, which may lead to increased CRC screening rates and decreased CRC incidence and deaths.